The Impact of Creativity, Leadership, Networking, and Organizational Innovation toward Organizational Performance on Content Creator Agency in Surabaya - Hananiel Gunawan; Napitupulu, Priscilla; Janice Siahaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study examines the impact of creativity, leadership, networking, and organizational innovation on organizational performance among digital content creators in Surabaya. As the creative digital economy grows rapidly, content creators face intense competition that demands not only creativity but also strategic management capabilities. Creativity is essential in producing unique and engaging content, while leadership shapes vision, direction, and motivation. While leadership provides direction and motivation for sustainable growth. Networking enables collaboration with peers, platforms, and clients, expanding market reach and resource access. Organizational innovation, meanwhile, drives continuous improvement in content, processes, and business models. Using a quantitative approach, data were collected from digital content creators operating in Surabaya and analyzed to test the relationships between the proposed variables. The findings are expected to highlight how these four strategic management dimensions contribute to enhanced organizational performance in the creative digital sector. This study provides both theoretical insights and practical implications for entrepreneurs, policymakers, and educators to strengthen the competitiveness of local digital content creators.